Pengaruh Profitabilitas, Umur Perusahaan, Ukuran Perusahaan, Kualitas Audit, Dan Struktur Modal Terhadap Kualitas Laba - Keshia Anjelica; Albertus Fani Prasetyawan (Ultima Accounting : Jurnal Ilmu Akuntansi, 2014)
The objective of this research is to examine the effect of profitability, firm age, firm size, audit quality, and leverage both partially and simultaneously towards earnings quality. The testing method used in this research is multiple regressions. The objects of this study are property, real estate and construction companies which were listed at Kompas 100 for the period 2010-2012. The samples are 15 companies determined based on purposive sampling. The data used in this study are secondary data such as financial statements and historical stock prices. The results of this study are (1) firm age has a negative significant effect on earnings quality, meanwhile firm size has a positive significant effect on earnings quality (2) profitability, audit quality, and leverage partially have an insignificant effect towards earnings quality (3) profitability, firm age, firm size, audit quality, and leverage simultaneously have a significant effect towards voluntary auditor switching. Keywords: ERC, earnings quality, profitability, firm age, firm size, audit quality, leverage.